Participatory Urban Governance in Bangladesh: A Study of the Gap between Promise and Realities - Swapan, Mohammad (Sage Publications India Pvt. Ltd., 2016)
The discourses of governance played a crucial role in shaping the institutional space of participation. However, the forms and structure of such discourses have given rise to debates on their appropriateness to reflect socio-political dynamics of South Asian countries and engaging citizens effectively. In recent years, participation in planning projects has been significantly low, indicating a significant gap between theory and practice. An in-depth investigation on embedded factors that affect participatory governance process can address this gap. In this article, I emphasize the theoretical foundations and practice shaping participatory urban development in developing countries. Effort has been made to reconnect planning practice with other cross-disciplinary issues such as policy research, public administration, political science and social science by investigating and analyzing the institutional and socio-political settings in Bangladesh. It further examines their strategic impacts on shaping the gap between expected and achieved levels of citizen engagements in urban planning projects. The study suggests that ineffective planning administration and public apathy derived from bureaucracy and top-down planning approach jointly lead to low level of citizen participation. In addition, parallel governance system based on informal socio-political network between privileged citizens and decision-makers leaves the formal governance system inactive.